(untitled) (Al-Farooq Journal of Sciences, 2026)
This research paper aims to provide a comprehensive review of the effectiveness of using probiotics to extend the shelf life of white cheese and improve its microbial and sensory properties. Dairy products, especially white cheese, are susceptible to rapid microbial spoilage, necessitating innovative solutions to maintain their quality and safety. Studies have shown that incorporating probiotics into the cheese matrix can significantly reduce the microbial load of spoilage organisms, enhance the sensory characteristics of the product, and thus contribute to increasing its shelf life. This paper reviews the mechanisms of probiotic action, the most important strains used, and the methods followed in evaluating their effectiveness, in addition to industrial challenges and future perspectives in this vital field.